Studies on Synthesis and Kinetic Hydrolysis of Chiral Organic Phosphoramidates by Suitable Methods - Ibomcha Singh, Soram; Prabha, Shashi (Asian Journal of Chemistry, 2011)
The study was focused on the nature of the substituents and their influence on the reactivity and the stability of the synthesized mixed chiral phosphoramidates. The ortho-chloro substituent has proved to be significant during hydrolysis resulting in maximum reactivity and also the presence of bulky groupings around the phosphorus atom hindered the approach of the nucleophile to a large extent, thereby resulting in the minimum rate of hydrolytic cleavage. The presence of dimethyl formamide has resulted in the deviation of the physiological conditions desired but no correlation could be tabled out for its influence on the rate of hydrolysis.